Flüssigprozessierte organische Tandem-Leuchtdioden - Höfle, Stefan (KIT Scientific Publishing, 2015)
In this work, printable organic tandem light emitting diodes for future cost-efficient, long-time stable and white light emitting devices are presented. The key to such multilayer devices is to develop charge carrier injection layers based on metal-oxides like WO3, MoO3, V2O5 and modified ZnO, which can be applied from precursors. Furthermore, these precursor-based approach enables the fabrication of OLED with inverted architecture as well as transparent light emitting diodes.